2018
DOI: 10.1016/j.scitotenv.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of hydrology, community ecology and pollutant attenuation in the hyporheic zone

Abstract: 1) We describe the hierarchical interplay of hydrology, hyporheic ecology and transformation of nutrients and pollutants in the hyporheic zone (HZ). The exchange of water between the surface-subsurface generates the hyporheic exchange flow: the engine that drives the ecological functioning of the HZ. The magnitude and direction of hydrological fluxes in the HZ follow complex spatial patterns, strongly influenced by the temporal dynamics of surface flow in rivers. 2) The direction and magnitude of hydrological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 126 publications
3
67
0
4
Order By: Relevance
“…The dramatic reduction in biomass and α‐diversity of Protozoa and Eumetazoa invertebrates within the HZ in this study supports the widely reported pattern of simplification of streambed communities with increasing depth in the streambed (e.g. Schmid‐Araya, ; Sliva & Williams, ; Andrushchyshyn, Wilson, & Williams, ; Reynolds & Benke, , Peralta‐Maraver, ; Dunscombe, Robertson, Peralta‐Maraver, & Shaw, ). Results from our regional‐scale approach are also in agreement with previous experimental assessments (Cornut et al, ) and local‐scale survey studies (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The dramatic reduction in biomass and α‐diversity of Protozoa and Eumetazoa invertebrates within the HZ in this study supports the widely reported pattern of simplification of streambed communities with increasing depth in the streambed (e.g. Schmid‐Araya, ; Sliva & Williams, ; Andrushchyshyn, Wilson, & Williams, ; Reynolds & Benke, , Peralta‐Maraver, ; Dunscombe, Robertson, Peralta‐Maraver, & Shaw, ). Results from our regional‐scale approach are also in agreement with previous experimental assessments (Cornut et al, ) and local‐scale survey studies (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Many ecological processes are related to hyporheic exchange, because this affects the substrate properties and water quality and produces physicochemical gradients to which macroinvertebrates are sensitive [9,10]. Therefore, hyporheic exchange not only provides key ecological processes [11], but more importantly affects the development of macroinvertebrate communities in river ecosystems [10,12]. Actually,…”
Section: Introductionmentioning
confidence: 99%
“…vegetation density, riparian, and in-channel vegetation) is considered in this review as the main ecological factor that influences HEF (Heppell et al, 2009;Corenblit et al, 2007). Although not reported in this paper, we acknowledge that other ecological factors such as hyporheic freshwater invertebrates and biofilm have a major role in interacting with HEF (Peralta-Maraver et al, 2018).…”
Section: Concepts and Terminologymentioning
confidence: 84%